1984
DOI: 10.1192/bjp.145.6.641
|View full text |Cite
|
Sign up to set email alerts
|

Marital Intimacy and Depression

Abstract: Recent research has suggested that the absence of an intimate, confiding relationship may be a vulnerability factor in the development of depression in women living under adverse circumstances. This study demonstrates a significant association between severity of depression and deficiencies of marital intimacy; depressed patients with the lowest levels of marital intimacy failed to improve at one month follow-up, while 36% of the spouses of the depressed patients had symptoms of non-psychotic emotional illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Brown and Harris (1978) identified the lack of a close, confiding relationship as a risk factor in the vulnerability to depression of women under adverse circumstances. Deficiencies in the quality and quantity of marital intimacy are significantly associated with severity of depressive symptoms in both clinical and nonclinical married women (Waring & Patton, 1984; . Marital discord is the most common life stressor that initiates episodes of depression (Paykel et al, 1969).…”
Section: Edward M Waring Charles H Chamberlaine Claudia M Carvementioning
confidence: 99%
“…Brown and Harris (1978) identified the lack of a close, confiding relationship as a risk factor in the vulnerability to depression of women under adverse circumstances. Deficiencies in the quality and quantity of marital intimacy are significantly associated with severity of depressive symptoms in both clinical and nonclinical married women (Waring & Patton, 1984; . Marital discord is the most common life stressor that initiates episodes of depression (Paykel et al, 1969).…”
Section: Edward M Waring Charles H Chamberlaine Claudia M Carvementioning
confidence: 99%
“…From the earliest studies that detected greater marital discord in marriages with a patient with SC (Weintraub, 1987) to current studies that have observed high rates of broken marriages and marital maladjustment in SC (Thara and Srinivasan, 1997a), the consensus is that marital adjustment dictates the course and the outcome of SC (Jablensky, 2009). Similarly, recurrent depressive disorders (RDDs) have been observed to have significant marital maladjustment (Akbiyik et al, 2008;Weintraub, 1987;Wells et al, 1989), with both outcome (Denton et al, 2010) and severity of depressive symptoms linked to severity of marital maladjustment (Heene et al, 2007;Waring and Patton, 1984). However, a study from similar settings in India observed poor marital adjustment in depressive disorders but found no evidence of its link to psychosocial functioning or QOL (Subodh et al, 2008).…”
mentioning
confidence: 95%
“…Better knowledge of important aspects of the marital relationship, such as the experience of intimacy, could contribute to the development of more effective marital enrichment programs and marital therapy, which in turn will have a positive effect on family and societal functioning. Facets of intimacy that are emphasized by researchers include intention, involvement, emotion, sexuality, and gender (Dandeneau & Johnson, 1994;Merves-Okin, Amidon, & Bernt, 1991;Robinson & Blanton, 1993;Schaefer & Olson, 1981;Thomson & Walker, 1989;Tolstedt & Stokes, 1983;Waring, 1981;Waring & Patton, 1984). Most definitions emphasize one or more of the following three characteristics: behavioral interdependency, fulfillment of needs, and emotional attachment (Brehm, 1992).…”
mentioning
confidence: 98%